Persistent and Recurrent Hyperparathyroidism After Total Parathyroidectomy With Autotransplantation - Chou, Fong-Fu (2002)
OBJECTIVE: To conduct a retrospective study of 15 patients with persistent (n = 4) and recurrent (n = 11) hyperparathyroidism. SUMMARY BACKGROUND DATA: Secondary hyperparathyroidism may persist or recur because of hyperfunction of the parathyroid remnant or transplanted parathyroid tissue. It is a great challenge to localize the parathyroid tissue either in the neck or at the arm before surgery. METHODS: From June 1994 to June 2000, 15 patients with recurrent and persistent secondary hyperparathyroidism were selected for surgery for the removal of parathyroid tissue. The indications for surgery included bone pain, hypercalcemia, general weakness, and skin itching. Their ages ranged from 23 to 66 years. The average period of persistent hyperparathyroidism after total parathyroidectomy with autotransplantation was 3.8 months; that of recurrent hyperparathyroidism was 53 months. Serum levels of calcium, phosphorus, parathyroid hormone (iPTH), and alkaline phosphatase were measured before surgery and 1 week after surgery. Before surgery, the parathyroid gradient in the blood draining the graft-bearing arm versus the contralateral arm was measured. A (99m)Tc-sestamibi (MIBI) scan was performed including the neck and the arm area, and a computed tomography (CT) scan of the neck was performed to confirm the localization. The neck and mediastinal exploration was done directly at the side of localization under general anesthesia to remove the parathyroid tissue that had been located with the MIBI scan or CT scan. An arm exploration was done under local anesthesia to remove all parathyroid tissues detected in the MIBI scan or palpable masses during surgery. If all glands were removed, 0.5 × 0.5 × 0.5 cm of tissue (60–100 mg) was maintained in situ or the same amount of tissue was reimplanted. RESULTS: The average ratio of iPTH in the graft-bearing arm to the contralateral arm in the 5 patients with parathyroid tissue in the neck was 1.17 ± 0.16, and that in the 10 patients with parathyroid at the arm was 14.15 ± 16.62. A significant difference was found between the two groups. MIBI scans showed parathyroid tissues in the neck in four of five patients and in seven of eight patients at the arm. Computed tomography showed the parathyroid tissues in the neck and mediastinum in five of five patients (100%). Five glands were removed from these five patients, three in the neck, one in the mediastinum, and one in the carotid sheath. In total, 20 glands and 2 half-glands were removed from 10 patients; among these, 14 glands were shown in the MIBI scan. All patients had improvements of symptoms and signs after surgery. Serum levels of calcium, phosphorus, and iPTH decreased rapidly after surgery, but alkaline phosphatase did not. CONCLUSIONS: With the results obtained from the ratio of iPTH of the graft-bearing arm to the contralateral arm, clinical palpation of the arm, MIBI scan, CT scan, careful surgical exploration, and adequate resection, recurrent and persistent secondary hyperparathyroidism can be successfully treated with surgery in the neck or at the arm.